Hubungan Tingkat Pengetahuan Gizi dan Tingkat Stres Dengan Status Gizi Remaja - Zainun Wahida Fithriani; Imroatus Sholihah (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2023)
Nutritional status of a person is an important aspect in determining for make quality life for someone. For get it the person must be good nutritional status and better knowledge for choosing, processing and digesting foods that are rich in nutrients. The health indicator for person is come be in nutritional status. Knowledge of nutritional status will determine the growth and development of each individual (Annisa Wulandari, Irfan Sudrajat, 2021). The purpose of this activity is to examine the relationship between knowledge level and stress level with adolescent nutritional status at STIKES Sukma Wijaya Sampang. This type of research is analytical descriptive research with a cross-sectional design where this research aims to decipher a state in a community which then explains the situation through collection. This study is a quantitative study to see the correlation between Nutritional Knowledge Level and Stress Level with adolescent nutritional status using spearman rank correlation test. The results showed p-value 0,04, there were a significant difference between knowledge and nutritional status (p=0,04), there were no significant between stress levels and nutritional status (p=0,711).